Strategi Komunikasi BPRPI Dalam Mengembalikan Tanah Jaluran Masyarakat Melayu Di Sumatera Utara - Tantry Widiyanartti; Munawar Holil (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
The purpose of this research is to look at  how Badan Perjuangan Rakyat Penunggu Indonesia (“Indonesian People Struggle Struggle Agency”) (BPRPI) conducted a communication strategy to restore land of the Malays in North Sumatera. The method used is descriptive qualitative. Data collection is done by observation, interview and literature from various sources. That the ways and strategies of communication undertaken by BPRPI in returning streetland to the Malay community is to use public spheres to build the Malay ethnicity issue, to build a collective memory discourse (ulayat rights land and ulayat land) using mass media as well as hybrid media, to disseminate the BPRPI’s struglgle to the public. The communication strategy of the BPRPI, received support from the Malay society, legally BPRPI won its struggle, but politically until now the goal to be achieved has not been fully realized right. Until now BPRPI continue to strugle to get the land of the street.Keyword: Communication strategy, BPRPI, street land (tanah jaluran), public sphere, media impact.